Living recovery : youth speak out on "owning" mental illness - Leavey, JoAnn Elizabeth (Waterloo, Ontario, Canada : Wilfrid Laurier University Press, 2015)
Living Recovery provides critical information for practitioners and educators in mental health services about the self-described needs of young people diagnosed with mental illness. It portrays the stages of living with mental illness through the recovery model ELAR-emergence, loss, adaptation, and recovery.
Includes bibliographical references and index.
Keywords: Youth with mental disabilities; Youth with mental disabilities -- Education; Youth with mental disabilities -- Services for